MOBILE-ASSISTED ON EXTENSIVE READING: STUDENTS’ VOICES - Ni'mah, Dzurriyyatun; Umamah, Atik (Universitas Nusantara PGRI Kediri, 2020)
Abstract As reading starts to lose its popularity for most students, digital reading can serve as a solution to overcome this problem. The integration of digital reading and extensive reading practice can be beneficial for language learners. A number of researchers have conducted the studies on this issue through different perspectives. The current study mainly focuses on the students’ perception of digital reading in extensive reading practice. The qualitative approach was employed to obtain the research data. Therefore, series of questions were addressed to achieve the research objective through an open-ended interview. The result showed that the students have positive attitudes towards digital reading when they have to read extensively. The practicality, portability, flexibility, accessability, and affordances of e-books helped them to apply extensive reading successfully. Moreover, extensive reading benefits the students to develop their reading habit, discover pleasure in reading, as well as improve other skills in English. Keywords: digital reading, extensive reading, students’ perception